2017
DOI: 10.1007/s10620-017-4550-x
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Epithelium-Derived Factor (PEDF) Prevents Hepatic Fat Storage, Inflammation, and Fibrosis in Dietary Steatohepatitis of Mice

Abstract: The present results demonstrated for the first time that PEDF could slow the development and progression of steatohepatitis through the suppression of steatosis and inflammatory response in MCD diet-fed mice. Our study suggests that PEDF supplementation may be a novel therapeutic strategy for the treatment of NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…However, the function of PEDF in the liver remains largely unknown. Studies have shown that PEDF has anti-oxidative capacities and protects hepatocytes from inflammation-induced cell death during NASH progression [14,16], suggesting that PEDF is an important hepatokine beyond merely being a lipolytic agent. In this study, we demonstrate that decreased PEDF expression, observed in the mouse fatty liver, enhances fatty acid uptake and resultant lipid accumulation and mobilization in vitro, with a concomitant increase in fatty acid transport proteins CD36 and FABP1, but not FATP2 and FATP4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the function of PEDF in the liver remains largely unknown. Studies have shown that PEDF has anti-oxidative capacities and protects hepatocytes from inflammation-induced cell death during NASH progression [14,16], suggesting that PEDF is an important hepatokine beyond merely being a lipolytic agent. In this study, we demonstrate that decreased PEDF expression, observed in the mouse fatty liver, enhances fatty acid uptake and resultant lipid accumulation and mobilization in vitro, with a concomitant increase in fatty acid transport proteins CD36 and FABP1, but not FATP2 and FATP4.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its pathogenic potential, PEDF seems to play a protective role in the liver. PEDF reduces high fat diet induced obesity and NAFLD progression through its antioxidant and anti-inflammatory capacity in several animal studies [14][15][16]. However, how PEDF regulates hepatic lipid accumulation remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…PEDF has been suggested to be a potential therapeutic agent in NASH and liver fibrosis putatively by directly inhibiting hepatic stellate cell activation or by upregulating matrix metalloproteinase 2 (19,20). In addition, knockout of PEDF or gene transfer to the liver also demonstrated its role in steatosis (21,42), although the precise molecular events underlying those results remain obscure. However, the role of PEDF in preventing hepatocyte ballooning or death, the pathognomonic hallmark that differentiates NASH from simple steatosis, has not yet been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…SOD1 induces Rac1 activity that in turn mediates NOX1 and then NOX4 activation . Rac1 is also involved in hepatic inflammation, and it is an important corollary for NOX2 activation …”
Section: Hscs Nox and Liver Fibrosismentioning
confidence: 99%